Community Policing: “Atalakpa” (Edo State Security Network) and the Management of Crime and Internal Security in Edo State, Nigeria - Idowu, Olusegun Oladele; Usifoh, Destiny Ebatamaehi Usifoh (African Journal of Stability and Development (AJSD), 2024)
This study assessed the praxis of community policing in managing internal security in Edo State, Nigeria. It also evaluated the nature of community policing (Atalakpa-Edo State Security Network) in Edo State and its effectiveness. In addition, the study identified the relationship between community policing (Atalakpa-Edo State Security Network) and the public security force in Edo state. The study further Identified the challenges confronting Atalakpa-Edo State Security Network in Edo State. The study employed survey research design, using both quantitative and qualitative research methods. Also, both primary and secondary data were explored. The data collected were analysed using descriptive statistics involving frequency counts, percentages, mean scores and charts. The findings showed that the government falls short of effectively providing security for the citizens; hence, the community opted for Atalakpa community policing, which is focused on fostering greater trust and cooperation between the police and the residents geared towards maximising police resources through community participation in public safety initiatives. The study concluded that the emergence of community policing (Atalakpa-Edo State Security Network) was borne out of the need to reduce crimes and social vices, security of lives and properties, and to complement other security agencies in fighting crime and criminality in rural areas. The study recommends restructuring and overhauling of the Atalakpa- Edo State Security Network to meet its establishment’s goals and purpose. Also, there should be better collaboration and partnership between community policing and other security agencies in the area of handing-over/transporting of suspects, conducting investigation, sharing of information, fire alert, armed patrol, joint duty posting, training and re-training; workshops and seminars, with a view to fighting crime and criminality, and entrenching peace in rural areas.